2010
DOI: 10.1007/s10554-010-9690-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of first generation dual-source computed tomography in the assessment of coronary artery disease: a meta-analysis from 24 studies

Abstract: The objective of this study is to evaluate the diagnostic accuracy of the first generation dual-source computed tomography (DSCT) in the diagnosis of coronary artery disease (CAD). We selected articles from four databases (Pubmed, Embase, the Cochrane central register of controlled trials (CENTRAL) and Chinese biomedical literature database. The strict study selection was made, and two reviewers independently extracted data back-to-back from included studies. Meta-Disc version 1.4 was used to obtain the pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 51 publications
1
19
1
Order By: Relevance
“…(32) Similarly, a metaanalysis of 24 studies showed that DSCT coronary angiography had high sensitivity and specificity for CAD, especially in patients with high heart rates. (34) Our results were consistent with these reports, as we too found that assessable segments in studies using DSCT coronary angiography were higher than those in studies using SSCT coronary angiography, although the difference was not statistically significant.…”
Section: Figsupporting
confidence: 92%
“…(32) Similarly, a metaanalysis of 24 studies showed that DSCT coronary angiography had high sensitivity and specificity for CAD, especially in patients with high heart rates. (34) Our results were consistent with these reports, as we too found that assessable segments in studies using DSCT coronary angiography were higher than those in studies using SSCT coronary angiography, although the difference was not statistically significant.…”
Section: Figsupporting
confidence: 92%
“…We defined significant CAD as C70 % stenosis in one or more vessels on CAG or CCTA. Although CAG is the reference standard test to define significant coronary artery stenosis, the high diagnostic accuracy of CCTA has been reported in many studies [25][26][27]. Among 69 patients who underwent coronary imaging tests in this study, 33 patients underwent CAG and 52 patients did CCTA.…”
Section: Discussionmentioning
confidence: 84%
“…3,5-7, 29,30 These analyses indicate that CCTA has high diagnostic value in the detection and characterization of CAD due to presence of plaques (Figure 1). Currently, 320-slice CT represents the recently technological developments in imaging coronary artery disease with good results achieved.…”
Section: Diagnostic Value Of Ccta In Cadmentioning
confidence: 92%